2014
DOI: 10.1128/aac.01803-13
|View full text |Cite
|
Sign up to set email alerts
|

Genomics of KPC-Producing Klebsiella pneumoniae Sequence Type 512 Clone Highlights the Role of RamR and Ribosomal S10 Protein Mutations in Conferring Tigecycline Resistance

Abstract: Full genome sequences were determined for five Klebsiella pneumoniae strains belonging to the sequence type 512 (ST512) clone, producing KPC-3. Three strains were resistant to tigecycline, one showed an intermediate phenotype, and one was susceptible. Comparative analysis performed using the genome of the susceptible strain as a reference sequence identified genetic differences possibly associated with resistance to tigecycline. Results demonstrated that mutations in the ramR gene occurred in two of the three … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
86
2
3

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(96 citation statements)
references
References 43 publications
5
86
2
3
Order By: Relevance
“…Therefore, as expected, no corresponding mutant could be obtained. In K. pneumoniae, it seems that the inactivation of the ramR gene (coding for an indirect negative regulator of the acrAB operon) is the most common mechanism conferring resistance to TIG (28). Nevertheless, it has recently been demonstrated that the resistance to TIG of the KPCproducing K. pneumoniae KP4-R strain was due to a Val57Leu substitution in the RpsJ protein sequence (28).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, as expected, no corresponding mutant could be obtained. In K. pneumoniae, it seems that the inactivation of the ramR gene (coding for an indirect negative regulator of the acrAB operon) is the most common mechanism conferring resistance to TIG (28). Nevertheless, it has recently been demonstrated that the resistance to TIG of the KPCproducing K. pneumoniae KP4-R strain was due to a Val57Leu substitution in the RpsJ protein sequence (28).…”
Section: Discussionmentioning
confidence: 99%
“…In K. pneumoniae, it seems that the inactivation of the ramR gene (coding for an indirect negative regulator of the acrAB operon) is the most common mechanism conferring resistance to TIG (28). Nevertheless, it has recently been demonstrated that the resistance to TIG of the KPCproducing K. pneumoniae KP4-R strain was due to a Val57Leu substitution in the RpsJ protein sequence (28). Moreover, as for the strains used in this study, the efflux did not appear to be involved in TIG resistance, pointing out that structural alteration of the ribosomal protein S10 in the drug target site may be a potential novel mechanism.…”
Section: Discussionmentioning
confidence: 99%
“…ramR is located upstream of the romA and ramA genes and is transcribed divergently (787), and RamR binds to two sites of the romA-ram locus (788). Mutations in ramR can yield hyperproduction of RamA and AcrAB-TolC (300,787,788). Another AraC regulator, RarA, which is encoded by a gene upstream of the chromosomal oqxAB pump genes (chromosomal oqxAB genes are found only in K. pneumoniae to date), also positively controls the expression of AcrAB and OqxAB.…”
Section: K Pneumoniae Efflux Pumpsmentioning
confidence: 99%
“…Isolates were considered related if there was a 0-or 1-band difference. Finally, select isolates of K. pneumoniae were also examined for mutations in genes encoding RamR and ribosomal S10 proteins, using previously described primers and PCR conditions (11).…”
mentioning
confidence: 99%